The Interrelation between the Interest Groups and Their Impact on the Economic Reforms in Modern Russia (beginning) - ЯковлевАндрей Александрович (Journal of Economic Sociology, 2010)
The logic of the paper is based on the thesis that the key questions for today Russian economic policy are the following: who can support the reforms and who can provide the stable economic growth as well as what mechanisms allow us to consolidate and motivate these social groups? With the help of critical analysis of the mass former studies the author shows that economic, social and political deformations that were accumulated during the Soviet period greatly predetermined the character of the elites’ transformation and the trajectory of the reforms in 1990s.